2008
DOI: 10.4062/biomolther.2008.16.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic-Like Effects of Cyclopeptide Fraction Alkaloids of Zizyphi Spinosi Semen: Possible Involvement of GABAAReceptors

Abstract: However, CFAZ has no effect on the locomotor activity, while diazepam (2.0 mg/kg, p.o.) significantly reduced locomotor activity. CFAZ did not influence the grip force in the grip strength meter test, either. From the molecular experiments, CFAZ increased chloride influx in cultured cerebellar granule cells. In addition, GABA A receptors γ-subunit were over-expressed by CFAZ in cultured cerebellar granule cells. It is concluded that CFAZ may have anxiolytic-like effects, and these effects may be mediated by GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…spinosa ) has been used as a tranquilizer, an anxiolytic and anticonvulsant in oriental countries, and also has been prescribed for the treatment of insomnia and anxiety ( Park et al ., 2004 ). It was reported that sanjoinine, which is a major alkaloid compound, and cyclopeptides from Semen zizyphi spinosae have have shown anxiolytic-like effects in the elevated plus-maze, hole-board test and open field test, and these effects may be mediated by GABA A -ergic transmission ( Han et al ., 2008 ). Sanjoinine A and cyclopeptide fraction from Semen zizyphi spinosae exert hypnotic effect and/or enhances pentobarbital-induced sleeping behaviors ( Ma et al ., 2008 ; Han et al ., 2009 ).…”
Section: Natural Products Which Have Proven To Be Effective For Sleepmentioning
confidence: 99%
“…spinosa ) has been used as a tranquilizer, an anxiolytic and anticonvulsant in oriental countries, and also has been prescribed for the treatment of insomnia and anxiety ( Park et al ., 2004 ). It was reported that sanjoinine, which is a major alkaloid compound, and cyclopeptides from Semen zizyphi spinosae have have shown anxiolytic-like effects in the elevated plus-maze, hole-board test and open field test, and these effects may be mediated by GABA A -ergic transmission ( Han et al ., 2008 ). Sanjoinine A and cyclopeptide fraction from Semen zizyphi spinosae exert hypnotic effect and/or enhances pentobarbital-induced sleeping behaviors ( Ma et al ., 2008 ; Han et al ., 2009 ).…”
Section: Natural Products Which Have Proven To Be Effective For Sleepmentioning
confidence: 99%
“…In addition, pentobarbital is well known to potentiate the effects of GABA by acting at its own binding sites on the GABA/benzodiazepine receptor ionophore complex [ 25 ]. Many hypnotic, antianxiety and antiepilepsy drugs have been shown to cause prolongation of pentobarbital-induced sleep time [ 26 28 ]. We were interested in whether EFC prolongs pentobarbital-induced sleep behaviors and interacts with pentobarbital in the CNS via the GABAergic systems.…”
Section: Discussionmentioning
confidence: 99%
“…At present, it is mainly believed that alkaloids and flavonoids in ZSS exert an antidepressant effect. By using the experimental paradigm of anxiety compared with the effects of a known anxiolytic, diazepam, it was concluded that the cyclopeptide alkaloids of ZSS may have anxiolytic-like effects, and these effects may be mediated by GABA A receptors . Sanjoinine A, one of the major alkaloid compounds in ZSS, was found to have anxiolytic-like effects in the elevated plus-maze, hole-board test, and open field test, and these effects may be mediated by GABAergic transmission .…”
Section: Biological Activities and Possible Health Benefitsmentioning
confidence: 99%